A ti, pranteio a minha dor: a morte e a expressão das emoções nos necrológios dos jornais impressos de Vitória (1849-1889) - Scolforo, Jória Motta (2022)
The main goal of this thesis is to carry out an analysis of necrologies, that is, the public homages published on the press after the death of someone, in three newspapers of periodic circulation in the city of Vitória, in Espírito Santo, between the years of 1849 and 1889, the “Correio da Victoria”, the “Jornal da Victoria”, and the “Espírito Santense”. Throughout this investigation, the representation of emotion was observed, thus verifying, in the sentimental and affective manifestations, the political relations and interactions seen on the texts. In this process, we read all of the available editions of the newspapers and we identified 76 necrologies consisting sensitive elements in order to carry out the verification according to the methodology of “Analysis of Content” by Dionne and Laville (1999). Our interest is in the reflection about the content of the lamentations, the value given to the personal biography and the search for comfort for the anguish which were demonstrated. Furthermore we pondered how the expression of emotion, apparently natural and usual in the human experience, is also a field for the occurence of power relations and disputes. The research was made on the 19th century because of the space that the writing about death occupied on the periodic newspapers and to the subjective and romantic way the eulogies were made. With the passage of time, mainly given the development and broadening of medicine and the change of rituals related to the dead, these characteristics were transformed and considerably reduced.